Rwanda Nutrition Expenditure and Institutional Review 2020 - Piatti-Fünfkirchen, Moritz; Liang, Liying; Akuoku, Jonathan Kweku; Mwitende, Patrice (World Bank, Washington, DC, 2020)
This report provides recommendations to further develop the methodology for nutrition expenditure analysis. This report carefully reviewed all available nutrition expenditure analyses available and drew methodological conclusions. Findings include a need for a standardized way of classifying nutrition-related spending to be applied, of which the 2013 Lancet Framework lends itself well. Government spending should be mapped against this framework to the extent possible. Government expenditure data as available from the FMIS should be used. Coding for nutrition should be done against activity descriptions in the budget. Merely looking at spending agencies or programs/subprograms is unlikely to be sufficiently precise to be helpful for an analysis and should only be used if the former not be available. Weighting nutrition spending tends to be subjective and should not be used for comparison. It is important to consider the adequacy of the institutional and public financial management environment. This can provide for actionable recommendations on how to improve the management of nutrition across governments, strengthen accountability, and help adjust spending toward high impact interventions. Optima can be used to inform allocative efficiency. It should however be interpreted with care if the unit cost estimates cannot be fully derived from Government and donor expenditure reports of all high impact interventions.